Identification of Two Lpp20 CD4+ T Cell Epitopes in Helicobacter pylori-Infected Subjects - Ning, Yunshan; Ye, Jianbin; Wen, Junjie; Wu, Danlin; Chen, Zhongbiao; Lin, Yanqing; Hu, Bingxin; Luo, Meiqun; Luo, Jun; Ning, Lijun; Li, Yan (Frontiers in Microbiology, 2018)
Antigen-specific CD4+ T cells play an essential role in effective immunity against Helicobacter pylori (H. pylori) infection. Lpp20, a conserved lipoprotein of H. pylori, has been investigated as one of major protective antigens for vaccination strategies. Our previous study identified two H-2d-restricted CD4+ T cell epitopes within Lpp20 and an epitope vaccine based on these epitopes was constructed, which protected mice in prophylactic and therapeutic vaccination against H. pylori infection. Immunodominant CD4+ T cell response is an important feature of antiviral, antibacterial and antitumor cellular immunity. However, while many immunodominant HLA-restricted CD4+ T cell epitopes of H. pylori protective antigens have been identified, immunodominant HLA-restricted Lpp20 CD4+ T cell epitope has not been elucidated. In this study, a systematic method was used to comprehensively evaluate the immunodominant Lpp20-specific CD4+ T cell response in H. pylori-infected patients. Using in vitro recombinant Lpp20 (rLpp20)-specific expanded T cell lines from H. pylori-infected subjects and 27 18mer overlapping synthetic peptides spanned the whole Lpp20 protein, we have shown that L55-72 and L79-96 harbored dominant epitopes for CD4+ T cell responses. Then the core sequence within these two 18mer dominant epitopes was screened by various extended or truncated 13mer peptides. The immunodominant epitope was mapped to L57-69 and L83-95. Various Epstein-Barr virus-transformed B lymphoblastoid cell lines (B-LCLs) with different HLA alleles were used as antigen presenting cell (APC) to present peptides to CD4+ T cells. The restriction molecules were determined by HLA class-Ⅱantibody blocking. L57-69 was restricted by DRB1-1501 and L83-95 by DRB1-1602. The epitopes were recognized on autologous dendritic cells (DCs) loaded with rLpp20 but also those pulsed with whole cell lysates of H. pylori, suggesting that these epitopes are naturally processed and presented by APC. CD4+ T cells were isolated from H. pylori-infected patients and stimulated with L57-69 and L83-95. These two epitopes were able to stimulate CD4+ T cell proliferation. This study may be of value for the future development of potential H. pylori vaccine.